Pengaruh Pendidikan dan Pelatihan (diklat) Terhadap Kinerja Guru di SMK Negeri 1 Sangatta Utara - Kamaria Kamaria; Ramdanil Mubarok; Anggra Prima (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
The purpose of this study is to quantify the degree to which teacher performance at SMK Negeri 1 Sangatta Utara is impacted by education and training (diklat). This study employs a field approach (field research) and quantitative methods. Questionnaires were given to respondents, in-person observations were made at the school, and documentation was completed in order to gather data. The whole teacher population of the school, or 62 teachers, participated in the survey. With the aid of SPSS version 16, data analysis was carried out using basic linear regression. The analysis's findings indicate a regression equation of Y = 3.296 + 0.897X and a correlation coefficient R of 0.804, which is categorized as extremely strong. This indicates that teacher performance is significantly improved by education and training. The 80.4% coefficient of determination indicates that training accounts for the majority of the variation in teacher performance, with other factors outside the scope of this study accounting for the remaining 19.6%. Thus, at SMK Negeri 1 Sangatta Utara, training is crucial to raising teacher performance.